Reject Biscuit as an Alternative of Feeding Materials to Improve Quality and Increase the Productivity of Milk in Smallholder Dairy Farms - Khotimah, Khusnul; ., Galih; ., Herwintono; Etti Tri Adiyastiti, Bayu (International Journal of Engineering and Technology, 2019)
Dairy milk in smallholder farms have an average 10-11 liters per days per lactation dairy cows and the milk quality of conventional farms have low production. One of the potential waste manufactures was reject biscuit or â€œcrackâ€. Cracks were still content nutrition of feed material. The aimed of this study was to determine using reject biscuit â€œcrackâ€ as one kind of feed materials in order to increase dairy milk production and alternative feed that the price can reached by smallholder farms. The materials used reject biscuit â€œcrackâ€ obtained from UBM and Garuda Food and the lactation dairy milk. The method used survey and experiment. The materials were used concentrate content crack and without crack, elephant grass, dairy cows strain Fries Holland (FH) and milk for sample. The data were analyzed descriptive qualitative. The result showed that milk of FH cows were given concentrate without crack (T1) had average of Value density = 1.023, dry matters = 11- 11.5% and milk volume = 8 liters/day/head, while given concentrate content crack with composition 50% concentrate content crack+ 50% concentrate without crack (T2) had the average of density = 1.024, dry matters = 11.5- 12,2% and milk volume = 8,6 liters/day/head, and it given 100% concentrate content crack (T3) had the average of density = 1.025, dry matters = 12.5- 14.9%, milk volume = 9,3 liter/day/head. The conclusion of the research were the concentrate content crack can increase productivity the amount of milk volume 16.66%, density value 8% and dry matters 26% when compared to the feed material without crack.Â